Problematika pelaksanaan pembelajaran IPAS kurikulum merdeka materi masyarakat yang beradab kelas IV sekolah dasar - Sintia Merna Sari; Sukarno Sukarno Sukarno; Matsuri Matsuri Matsuri (Didaktika Dwija Indria, 2023)
This qualitative descriptive research study focuses on the implementation of the IPAS curriculum for free material civilized society class IV SDN 01 Plumbon in 2022/2023. The study uses purposive sampling techniques, observation, documentation study interviews, and creswell data analysis to analyze the learning outcomes. The results show that differential learning is not optimal, and teachers face challenges such as passive interaction and less attention. Students also face issues like lack of IPAS accompanying books and disturbances in focus. To address these issues, the study recommends using varied learning methods, following seminars, and providing support and feedback. The study also examines learning outcomes through formative and summative assessments, with an average formative value of 81 and an average summative value of 77.5.